Komplikasi Kehamilan dan Persalinan Pada Kondisi 4 Terlalu di Puskesmas Jabung Kabupaten Malang - Al Isnaini, Likanatun Chotimah; Panggayuh, Ardi; Aristina, Nur Eva (Politeknik Kesehatan Kemenkes Malang (State Health Polytechnic of Malang), 2020)
Complications of pregnancy and childbirth are a contributing factor in maternal mortality due to being at â€œ4 extreme conditionsâ€ (too young, too old, too close to birth spacing, and too much). This research aimed to to show the description of pregnancy and childbirth complications at â€œ4 extreme conditionsâ€ in Puskesmas Jabung, Malang Regency. This research used a descriptive design with a retrospective approach. The research population was all pregnant and childbirth women with 4 extreme conditions who experienced complications of pregnancy and childbirth and were recorded in the mother cohort and labor report books from January 1 to September 30 2019 with total sampling technique, obtained a sample of 52 respondents. The research instrument used data collection tables to identify complications of pregnancy and childbirth that occurred in each respondent. Data analysis used univariate analysis by processing data into percentages. The results showed that the most pregnancy complications were anemia (59%), pre-eclampsia / eclampsia (31%), and multiple complications in pregnancy are anemia and pre-eclampsia / eclampsia (10%), while the most labor complications were preterm birth ( 42%), postpartum hemorrhage (25%), prolonged labor (19%), premature rupture of membranes (8%), and multiple complications are premature rupture of membranes and preterm birth and prolonged labor and postpartum hemorrhage, respectively 3%. Anemia and preterm birth are the highest incidence of pregnancy and childbirth complicatios at 4 extreme condition. Based on the results of this studies should be material information or insight for the community, especially women and families to consider planning the right time to get pregnant. Keywords: Pregnancy Complications, Childbirth Complications